A micro-extraction method for use with 4 mm plate geometry in the Dynamic Shear Rheometer to evaluate asphalt binder rheology. (20th August 2020) - Filonzi, Angelo; Lee, Sang Ki; Ferreira, Wellington; Hajj, Ramez; Bhasin, Amit
Highlights: A method to extract and recover asphalt binder from a small sample of mix or RAP. Low temperature properties of samples from this method can be evaluated using DSR. Proposed method correlates very well with traditional extraction and recovery methods. Low temperature properties of RAP vary substantially with the source of the RAP. Abstract: Current procedures to extract and recover asphalt binders require a large amount of material and consequently a large volume of toxic solvents. To reduce exposure and consumption of such solvents, a micro-extraction method for extracting and recovering asphalt binder from small amounts of asphalt mix or reclaimed asphalt pavement (RAP) is presented. Sixteen laboratory long term aged mixes were used to extract the binder and evaluate its properties, using both the micro-extraction and conventional extraction methods. The Bending Beam Rheometer (BBR) and Dynamic Shear Rheometer (DSR) with the 4 mm parallel plate geometry were used to determine the low temperature properties of the extracted materials. The DSR was used with samples obtained using the conventional extraction method and proposed micro-extraction method. Low temperature properties from the three different procedures (conventional extraction with BBR, conventional extraction with DSR, and micro-extraction with DSR) were compared. Results indicate that the 4 mm plate method is a viable surrogate to measure low temperature properties in lieu of the BBR for recovered and recycled materials. The combined use of micro-extraction and 4 mm parallel plate geometry is a viable technique to extract binder from small amounts of asphalt materials. The combined micro-extraction and 4 mm method was also used to demonstrate the high variability (up to 12 °C low continuous grade) among different RAP stockpiles collected from across the state of Texas.